Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Tardin, Rodrigo; Maricato, Guilherme; Kiszka, Jeremy J.; Cantor, Mauricio; Maciel, Israel; Melo-Santos, Gabriel; May-Collado, Laura; Meirelles, Ana Carolina; Gonçalves, Maria Isabel C.; Daura-Jorge, Fábio G.; Sousa-Lima, Renata S.; Le Pendu, Yvonnick; et al. (Elsevier, 2025)
Ocean warming, acidification, and deoxygenation are expected to intensify without significant climate mitigation. In the tropics, rising ocean temperatures may push marine species to their thermal limits, leading to redistributions and cascading effects on communities and ecosystems. We evaluate how future climate change scenarios could impact the habitat suitability of an endemic species of the western tropical Atlantic Ocean, the Guiana dolphin, Sotalia guianensis. Using data from systematic surveys conducted between 1987 and 2023 complemented by open-source databases, we built the most comprehensive occurrence dataset for the species and developed ensemble Species Distribution Models to predict future distributions under the latest CMIP6 projected scenarios—‘optimistic’ (SSP1-2.6), ‘intermediate’ (SSP2-4.5), ‘pessimistic’ (SSP5-8.5)—using expert knowledge to validate model predictions in the present. Our models project substantial range contractions under all climate scenarios. By 2070, under the pessimistic scenario, suitable habitat is expected to decline by 46.9 %, nearly doubling the habitat loss projected under the optimistic scenario (23 %). Guiana dolphins are expected to lose habitat in northeastern Brazil and along the Caribbean coast (except Costa Rica). Remaining suitable areas are expected to become fragmented and confined to southeastern and southern Brazil, where the coastal zone is the most urbanized and degraded. Currently, only 21.6 % of the predicted Guiana dolphin range overlaps with Marine Protected Areas (MPAs), and just 1.8 % is covered by MPAs that prohibit extractive activities—a small proportion expected to decline from 19 % to 14 % in the future. Our study highlights the urgent need to incorporate climate change into conservation strategies for coastal tropical marine predators.